Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur Yang Terdaftar Di BEI - Christian Kartolo, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to obtain empirical evidence regarding the effect of leverage, liquidity, company growth, and profitability on the value of the company in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. This study uses 67 manufacturing companies that have been selected through a purposive sampling method with a total of 201 data for three years. The data used are secondary data in the form of financial statements. Processing data in this study using SPSS 23. The results of the study show that leverage has a significant and positive effect on firm value, liquidity has a significant and positive effect on firm value and profitability has a significant and positive influence on firm value while firm growth (growth) has a significant effect but negative for company value.